Dimensional accuracy of different impression techniques of partially edentulous mandibular arch - VITTI,Rafael Pino (2017)
ABSTRACT Objective: The purpose of this in vitro study was to assess and compare the dimensional accuracy of three impression techniques: 1-step putty/light-body, 2-step putty/light-body, and the monophase technique. Methods: A partially edentulous standard stainless steel mandibular arch cast with reference points on the teeth was used to make the impressions. The anteroposterior and transverse distances were measured. All impressions were made with a polyvinyl siloxane using stock metallic (1- and 2-step putty/light-body techniques) or acrylic resin (monophase technique) trays. The monophase impressions were made using a light-body material and the 1- and 2-step putty/light-body impressions with putty and light-body materials. After impression procedures, the accuracy of each technique was assessed measuring the stone casts (n = 5) poured from the impressions using a microscope at 30x magnification and at 0.5 µm accuracy. The data were analyzed statistically using 2-way ANOVA and Tukey's test (p<0.05). Results: Stone casts made by all techniques had significantly negative linear changes (shrinkage). The anteroposterior distances showed more dimensional changes than the transverse distances. The edentulous side showed more shrinkage than the anteroposterior side. Conclusion: No differences between the impression techniques were found, but significant dimensional changes were observed.